Design and Implementation of Axial Flux Induction Motor Single Stator - Single Rotor for Electric Vehicle Application - Mochamad Ashari; Heri Suryoatmojo; Dedet Candra Riawan; Ronny Mardiyanto; D Fahmi; S Hidayat; K B Adam (Institut Teknologi Sepuluh Nopember, 2014)
Induction motor is suitable for the prime mover of the electric vehicle since the design the electric vehicle required extra slim and compact design. Therefore, this research proposes an axial flux induction motor consists of thinstator and rotor. This research will explain about the mechanical, electrical design and implementation of the axial fluxinduction motor that consists of single stator and single rotor. Basically, the design of this machine is similar to conventionalelectric motor. The differences are on the direction of the flux and its construction. The proposed motor has 500 W inputpower, low carbon material of core and the input voltage for this motor is 100 V. Material of the motor core is made fromsteel sheet st.37. The length of axial motor is 66 mm and diameter is 200 mm. From experimental results with the inputvoltage of 15 V, the rotor is able to rotate until 1366 RPM. In order to analysis the performance of the motor, simulationmodel based experimental data of the motor is required. The curve characteristic of the motor shows that the maximumtorque of the motor is 0.79 Nm.